Leadership skills for maintenance supervisors and managers - Levitt, Joel, 1952- (Boca Raton, FL : CRC Press, 2020)
"Supervision is a leveraged activity. When we develop the supervisor, we enhance the productivity of the whole workgroup. This book teaches both the science and the art of supervision of maintenance workers including essential management, necessary people skills, and the elements of technical issues. This book provides valuable skill training for supervisors, team leaders, and managers. It offers techniques to improve reliability that can be accomplished at the supervisor level. It teaches both the science and the art of supervision of maintenance workers, discusses managing meetings and time, and presents management and people skills which offer maximum productivity and high-quality provision of services and at the same time, improving morale throughout the workforce. This book is suitable for all types of maintenance for organizations with supervisors and managers from plant operations, storeroom, construction, and related areas including industrial organizations, construction companies, mines, fleets, building maintenance, janitorial maintenance contractors, and vocational tech schools teaching maintenance short courses"--
OCLC-licensed vendor bibliographic record.
Keywords: Industrial management; Supervisors -- Training of; Employee maintenance; Organizational effectiveness; TECHNOLOGY / Manufacturing; BUSINESS & ECONOMICS / Facility Management; BUSINESS & ECONOMICS / Leadership